Development of synthetic high-density lipoprotein-based ApoA-I mimetic peptide-loaded docetaxel as a drug delivery nanocarrier for breast cancer chemotherapy - Miaomiao Gong; Qi Zhang; Qi Zhao; Jiani Zheng; Yue Li; Siling Wang; Yue Yuan (Taylor & Francis Group, 2019)
In this study, a synthetic high-density lipoprotein (sHDL), peptide-based nanocarrier loaded with docetaxel (DTX) was constructed, against breast cancer. The thermodynamic and molecular dynamic analyses were conducted to examine the stability of nanoparticles synthesized from mimetic peptide 5 A and various types of phospholipids. Furthermore, the cellular uptake and in vivo fluorescence imaging analysis experiments, with scavenger receptor B-I (SR-BI) were carried out to examine the tumor-targeting ability of sHDL. The nanoparticles were investigated for their pharmacodynamic and cytotoxic effects to show their effectivity as anti-tumor agents. The results showed that the synthesized sHDL nanoparticles exhibited a high payload of DTX, sustained drug release properties, and excellent biocompatibility. Moreover, DTX-sHDL nanoparticles enhanced the uptake of DTX, increased the cytotoxicity against MCF-7 cells, and reduced the off-target side-effects to normal cells. Finally, experiments in 4T1 cell line-bearing mice indicate that inhibition of tumor growth by DTX-sHDL nanoparticles was superior to that of free DTX group. Thus, the sHDL nanoparticles are a promising drug delivery vehicle for improving the efficacy of anti-cancer drugs.